2020
DOI: 10.3390/nu12092521
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Vitamin D Treatment on Dynamics of Stones Formation in the Urinary Tract and Bone Density in Children with Idiopathic Hypercalciuria

Abstract: Vitamin D supplementation in patients with urolithiasis and hypercalciuria is considered to be unsafe. We analyzed the impact of vitamin D supplementation on selected health status parameters in children with idiopathic hypercalciuria. The study included 36 children with urolithiasis resulting from excessive calcium excretion. The level of calcium and 25(OH)D (hydroxylated vitamin D - calcidiol) in serum, urinary calcium excretion and the presence of stones in urinary tract were assessed prospectively. Blood a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Fallahzadeh et al [14] found serum levels of 25(OH)-vitamin D to be significantly higher in the infants with urolithiasis than in the controls, as well as positive correlation between serum levels of 25(OH)-vitamin D and serum calcium. Milart et al [24], studying children with hypercalciuria, observed a rise in serum 25(OH)-vitamin D following supplementation with vitamin D but no increase in calcium excretion. An extensive literature search concluded that the effect of oral vitamin D on urine calcium may vary between populations [23].…”
Section: Causes and Prognosis Of Infantile Urolithiasismentioning
confidence: 99%
“…Fallahzadeh et al [14] found serum levels of 25(OH)-vitamin D to be significantly higher in the infants with urolithiasis than in the controls, as well as positive correlation between serum levels of 25(OH)-vitamin D and serum calcium. Milart et al [24], studying children with hypercalciuria, observed a rise in serum 25(OH)-vitamin D following supplementation with vitamin D but no increase in calcium excretion. An extensive literature search concluded that the effect of oral vitamin D on urine calcium may vary between populations [23].…”
Section: Causes and Prognosis Of Infantile Urolithiasismentioning
confidence: 99%
“…The genetic background is also involved in the pathogenesis of IH. It has been described that patients with UL due to hypercalciuria can be carriers of genetic polymorphisms that encode certain proteins involved in the tubular reabsorption of calcium and phosphate (VDR, SLC34A1, SLC34A4, CLDN14, CaSR, TRPV6), or in the prevention of it precipitation of calcium salts (CaSR, MGP, OPN, PLAU, UMOD)[ 67 - 69 ]. Garcia Nieto et al [ 23 ] published a summary with all the pathophysiological mechanisms involved in IH described to date (Figure 1 ).…”
Section: Pathogenesis Of Hypercalciuriamentioning
confidence: 99%
“…This supplementation has been related to hypercalciuria. Milart et al [ 69 ] analyzed the impact of vitamin D supplementation on 36 children with IH and UL prospectively. Blood and urine samples were collected every three months up to 24 mo of vitamin D intake at a dose of 400 or 800 IU/d.…”
Section: Pathogenesis Of Hypercalciuriamentioning
confidence: 99%
“…Interventional studies showed no effect of cholecalciferol on body weight reduction in obese children participating in a weight management program [14], or on bone mineral density in children with hypercalciuria [15]. This last study emphasizes the safety of vitamin D treatment (400-800 IU/day) on calciuria and on the evolution of stones in the urinary tract in these children [15]. In post-menopausal women, ergocalciferol 40,000 IU/week did not change vulvovaginal atrophy compared to placebo, but improved vaginal pH and visual analog scale of vulvovaginal atrophy symptoms between baseline and 12 weeks in the vitamin D group [16].…”
mentioning
confidence: 99%
“…Regarding 25OHD assessment, it is specified that the detection of 3-Epi25(OH)D 3 using liquid chromatography-tandem mass spectrometry prevents the overestimation of 25OHD and misclassification of vitamin D status [11]. Interventional studies showed no effect of cholecalciferol on body weight reduction in obese children participating in a weight management program [14], or on bone mineral density in children with hypercalciuria [15]. This last study emphasizes the safety of vitamin D treatment (400-800 IU/day) on calciuria and on the evolution of stones in the urinary tract in these children [15].…”
mentioning
confidence: 99%